2019
DOI: 10.3390/ijms20102487
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Natural Killer T Cells and Natural Killer Cells in Kidney Injury

Abstract: Mouse natural killer T (NKT) cells and natural killer (NK) cells are innate immune cells that are highly abundant in the liver. In addition to their already-known antitumor and antimicrobial functions, their pathophysiological roles in the kidney have recently become evident. Under normal circumstances, the proportion of activated NKT cells in the kidney increases with age. Administration of a synthetic sphingoglycolipid ligand (alpha-galactosylceramide) further activates NKT cells, resulting in injury to rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…Studies have shown that sepsis induced AKI is accompanied by destruction of the immune system [23], and unconscionable apoptosis of immune cells can exacerbate sepsis and increase the mortality rate of patients. A grave inflammatory response induced by LPS stimulates neutrophils to emancipate numerous of pro-inflammatory cytokines, which have been reported to play pivotal roles in the pathogenesis of AKI [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sepsis induced AKI is accompanied by destruction of the immune system [23], and unconscionable apoptosis of immune cells can exacerbate sepsis and increase the mortality rate of patients. A grave inflammatory response induced by LPS stimulates neutrophils to emancipate numerous of pro-inflammatory cytokines, which have been reported to play pivotal roles in the pathogenesis of AKI [24].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CD4+ T cells and CD4+ T cells secreting interferon-gamma (IFN-γ) positive lymphocytes could participate in immune response of HIV infection and mycoplasmal infection [ 5 7 ]. Similarly, the accumulation of multifarious immune cells including NKT cells, CD4+ T cells, B cells and IFN-γ-producing neutrophils are closely associated with the pathogenesis of AKI [ 8 10 ]. Lipopolysaccharide (LPS)-induced sepsis is a primary cause of AKI in critically ill patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limited NK cell research exists in other major organs such as kidneys, heart, and others [ 70 , 71 ], but they show that NK cells play substantial roles in both immune protection and/or tissue injury in the inflammatory pathogenesis of renal and cardiovascular diseases. While the peripheral immune responses and parameters are useful in generating disease outcome predictors for COVID-19, knowledge of immune cell responses at the local and mucosal tissue microenvironment are even more critical for viral control and limiting severity of disease.…”
Section: Nk Cells At Sites Of Sars-cov-2 Infectionmentioning
confidence: 99%